The Influence of Interest in Becoming a Teacher and Experience in Participating in the Campus Teaching Program on the Readiness of Prospective Professional Teachers of UMS FKIP Students - Tsany, Amirah; Bambang Sumardjoko (Indonesian Journal Publisher, 2024)
The purpose of this study was to see how the involvement of interest in becoming a teacher and the experience of participating in the Campus Teaching Program affect the readiness of prospective professional teachers of FKIP UMS students. This study is a correlational study and was conducted in the Campus 1 environment, Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta. The population consisted of 325 students who had participated in the Campus Teaching program batch 6 and 7 , with a sample of 65 students. Information on the readiness of prospective professional teachers of students was obtained through a questionnaire. The t-test and F-test were used in data analysis to identify partial and simultaneous effects. The findings of the study indicate a strong and good correlation between interest in becoming a teacher, experience in participating in the Campus Teaching program, and the readiness of prospective professional teachers of students. Interest in becoming a teacher and experience in participating in the Campus Teaching program contributed 57,5% to the readiness of prospective professional teachers of students, while factors not included in this study contributed 42,5% to the variation. This study suggests looking at additional variables that influence the readiness of prospective professional teachers in more detail.